Exploring siRNA Umpired Nanogels: A Tale of Barrier Combating Carrier - Kashaw, Sushil K.; Sahu, Prashant; Rajoriya, Vaibhav; Jana, Pradeep; Kashaw, Varsha; Sau, Samaresh; Iyer, Arun K. (Current Pharmaceutical Design, 2020)
Potential short interfering RNAs (siRNA) modulating gene expression have emerged as a novel therapeutic arsenal against a wide range of maladies and disorders containing cancer, viral infections, bacterial ailments and metabolic snags at the molecular level. Nanogel, in the current medicinal era, displayed a comprehensive range of significant drug delivery prospects. Biodegradation, swelling and de-swelling tendency, pHsensitive drug release and thermo-sensitivity are some of the renowned associated benefits of nanogel drug delivery system. Global researches have also showed that nanogel system significantly targets and delivers the biomolecules including DNAs, siRNA, protein, peptides and other biologically active molecules. Biomolecules delivery via nanogel system explored a wide range of pharmaceutical, biomedical engineering and agro-medicinal application. The siRNAs and DNAs delivery plays a vivacious role by addressing the hitches allied with chronic and contemporary therapeutic like generic possession and low constancy. They also incite release kinetics approach from slow-release while mingling to rapid release at the targets will be beneficial as interference RNAs delivery carriers. Therefore, in this research, we focused on the latest improvements in the delivery of siRNA loaded nanogels by enhancing the absorption, stability, sensitivity and combating the hindrances in cellular trafficking and release process.
Keywords: gene expression